#Socialmedia: A Preliminary Report of Social Networking Use Among University and College Counseling Center Mental Health Providers. Issue 3 (3rd July 2017) - Reif, Carrie; Much, Kari
ABSTRACT: The social networking use of university and college counseling center (UCCC) mental health providers has not been widely researched. Most of the 20 providers surveyed in this preliminary study reported engaging in social networking despite identifying pros and cons to its use. Participants' reported use of social media may indicate that social networking sites are used primarily to glean information. Risks associated with social networking for UCCC practitioners are discussed and implications for training and social media use are provided.